Using the Energy and Momentum Conceptual Survey to investigate progression in student understanding from introductory to advanced levels - Mary Jane Brundage; Alexandru Maries; Chandralekha Singh (Physical Review Physics Education Research, 2023)
The Energy and Momentum Conceptual Survey (EMCS) is a multiple-choice survey that contains conceptual problems involving a variety of energy and momentum concepts covered in a typical introductory physics course for science and engineering majors. Prior studies suggest that many concepts on the survey are challenging for introductory physics students and the average student scores after traditional lecture-based instruction are low. The research presented here investigates the progression in student understanding of the EMCS concepts including their evolution from the beginning to the end of their courses in introductory and advanced-level undergraduate physics after traditional lecture-based instruction. We find that on all EMCS questions on which less than 50% of the introductory physics students answered a question correctly after traditional instruction, less than two-thirds of the upper-level undergraduate students provided the correct response after traditional lecture-based instruction. We discuss the EMCS questions that remain challenging and the common alternate conceptions among upper-level students. The findings presented here are consistent with prior research showing that traditional instruction in upper-level courses, which typically focuses primarily on quantitative problem solving and often incentivizes the use of algorithmic approaches, is not effective in helping many students develop a functional understanding of underlying concepts.